2002
DOI: 10.1021/bp020042m
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐Carrying Polymeric Nanofibers Prepared via Electrospinning for Use as Unique Biocatalysts

Abstract: Improvement of catalytic efficiency of immobilized enzymes via materials engineering was demonstrated through the preparation of bioactive nanofibers. Bioactive polystyrene (PS) nanofibers with a typical diameter of 120 nm were prepared and examined for catalytic efficiency for biotransformations. The nanofibers were produced by electrospinning functionalized PS, followed by the chemical attachment of a model enzyme, alpha-chymotrypsin. The observed enzyme loading as determined by active site titration was up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
216
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(223 citation statements)
references
References 88 publications
1
216
0
6
Order By: Relevance
“…The particles are biocompatible, have the ability to be conjugated to molecules without af-fecting the core and also can be used to encapsulate drugs 1 . Various micro/nano carriers, particularly nanoparticles and nanofibers, have become available for enzyme immobilization 4,5 . Typically, smaller particles provide a larger surface area for the attachment of enzymes 6 and a shorter diffusional path for the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The particles are biocompatible, have the ability to be conjugated to molecules without af-fecting the core and also can be used to encapsulate drugs 1 . Various micro/nano carriers, particularly nanoparticles and nanofibers, have become available for enzyme immobilization 4,5 . Typically, smaller particles provide a larger surface area for the attachment of enzymes 6 and a shorter diffusional path for the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…143 The catalytic activity of palladium (Pd)-incorporated nanofibres for selective hydrogenation of dehydrolinalool was found to be 4.5 times higher than the Pd catalyst supported on Al 2 O 3 powders. 130 It was observed that the intensity of light scattered from nanofibres was dependant on the polarization direction of light.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…To achieve high enzyme loading and catalytic efficiency of enzymes for large-scale operation and application, polymer nanofibers have attracted continuous attention for their unique properties (39,40). Compared with other nanostructured supports (e.g.…”
Section: Enzyme Immobilization On Nanofibersmentioning
confidence: 99%